VEGETASI POHON DAN PERSEBARANNYA DI TAMAN WISATA ALAM GUNUNG TUNAK DAN HUTAN KERAMAT, MANDALIKA, LOMBOK TENGAH, PROVINSI NUSA TENGGARA BARAT - Muhammad Mansur (Research Center for Biology-Indonesian Institute of Sciences, 2020)
The study was conducted on March 2018 in two locations study, i.e. Mount Tunak Nature Tourism Park (NTP) (6400 m2 plot area) and Keramat Forest (4800 m2 plot area), Central Lombok District, West Nusa Tenggara Province. The objective of the study was to find out the diversity of tree species and its distribution which can be used for forest area management by the local government and can support the establishment of a Special Economic Region in Mandalika as a place for conservation, research, education and scientific tourism. In the total plot of 1.12 hectare, we recorded 1560 individuals, representing 56 species, 47 genera and 19 families. All stems ≥ 5 cm in diameter were measured and identified. In the plot of Mt. Tunak NTP, we recorded 992 individuals, representing 41 species, basal area was 11.4 m2, 31.7 m3of estimated bole volume, 78.3 tons biomass, 39.2 tons carbon stock and 143.7 tons CO2 sequestration. Five dominant tree species (trunk diameter ≥ 5 cm) recorded with the highest Importance Value Index (IVI) were Aglaia argentea (IVI= 34.3%), Schoutenia ovata (IVI= 33.3%), Drypetes neglecta (IVI= 25.4%), Glycosmis pentaphylla (IVI= 16.4%) and Grewia koordersiana (IVI= 14.9%). The level of diversity of tree species in the Mt. Tunak NTP was classified into a midle level with a Diversity Index (H')= 3.3, while in the Keramat Forest we recorded 568 individuals, representing 37 species, basal area was 19.9 m2, 51.1 m3 of estimated bole volume, 149.8 tons biomass, 74.9 tons carbon stock and 274.9 tons CO2 sequestration. Five dominant tree species were recorded; Dalbergia latifolia (IVI= 69.4%), Grewia koordersiana (IVI= 34.5%), Schoutenia ovata (IVI= 34.3%), Cupaniopsis macropetala (IVI= 18.2%) and Rhus succedanea (IVI= 14.2%). The level of diversity recorded (H')= 2.9 and classified as midle level. The composition of vegetation in Mt.Tunak NTP and Keramat Forest is different (Jaccard Similarity Index was 39.3%).